Landasan teologis pendidikan Islam dalam Q.S. Al-‘Alaq Ayat 1–5: Prinsip-prinsip fundamental dan relevansinya terhadap tantangan pendidikan Modern - Adya Rafani Prima; Sarwadi Sulisno (Jurnal Pendidikan Agama Islam, 2026)
Al-‘Alaq verses 1–5 as fundamental principles within Islamic educational philosophy. As the first revelation sent by Allah to Prophet Muhammad through the Angel Jibril, Surah Al-‘Alaq emphasizes the urgency of seeking knowledge. This research aims to analyze the meaning of these verses, explain their theological implications for education, describe the educational concepts embedded within them, and explore their relevance in addressing contemporary educational challenges. This study employs a qualitative library research method. The data sources are divided into two categories: primary data derived from classical and modern tafsir that discuss QS. Al-‘Alaq 1–5, and secondary data consisting of books and scholarly journals relevant to the topic. The findings reveal that QS. Al-‘Alaq verses 1–5 contain four fundamental principles of Islamic education: (1) the command to seek knowledge, (2) education grounded in the doctrine of tawḥīd, (3) the recognition of human nature and innate potential (fiṭrah), and (4) the importance of learning media in the teaching learning process. These verses are also highly relevant in responding to educational issues today, particularly the crises of literacy, morality, and low learning motivation. Therefore, QS. Al-‘Alaq 1–5 as the first revelation serves as a comprehensive theological foundation for Islamic education and offers solutions to various challenges faced by modern educational systems.